Walking Corpse Syndrome: A trauma-related idiom of distress amongst Sri Lankan Tamils. (August 2022) - Affleck, William; Thamotharampillai, Umaharan; Hinton, Devon
This article introduces Walking Corpse Syndrome, a common idiom of distress in Tamil Sri Lanka that is characterized by a variety of cognitive difficulties, feelings that an individual is functioning reflexively or impulsively, and acute attacks of dissociation that are accompanied with the sensation of empty-headedness. Walking Corpse Syndrome demonstrates some overlap with Western nosology, although it appears to be its own unique illness category, most likely of Ayurvedic provenance. The article comprises two studies. One is a secondary interview analysis of community members that aimed to identify the key symptoms of Walking Corpse Syndrome, allowing us to determine the local ethnopsychology of the syndrome and to elicit illustrative vignettes. The other study is a survey of Sri Lankan Tamil psychiatrists that aimed to investigate their understanding and experience of the disorder. This article outlines how, in certain cultural contexts, such syndromes emphasise the loss of attentional capacity and forgetfulness; it highlights the importance of "thinking a lot" as an idiom across cultures; and it details the many ways that Walking Corpse Syndrome is a key idiom of distress to assess in order to give adequate mental healthcare to Sri Lankan Tamil populations.